Factors Motivating students to learn English at the Souphanouvong University, Faculty of Education, Department of English - SIDAVONG, Khanthaly (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This study investigated the factors motivating students to learn English at the Department of English, Faculty of Education, Souphanouvon University. The study aims were conducted to find out the factors that motivate students the most to learn English at Department of English. In addition, the study was also to compare the factors motivating year 2-3 students to learn English. The participants in this study were 110 students of year 2-3 students at the Department of English, in the FOE. The research methods employed in this study included quantitative method; the study employed a set of questionnaires for students, which consisted of 50 items. The questionnaires were adapted from Al-Lafi (2011), Lai (2013), and Tahaineh and Daana (2013) comprised of three parts with two types of questions, for instance, the multiple choice and open-ended. And then the data was analyzed through the SPSS (17.0); which calculated mean scores, average mean scores and standard deviations of 4 motivating factors based on 4-point rating scales for finding out what factor that motivate students to learn English the most and for comparing the factors that motivate year 2-3 students to learn English. The results of the study found that the strongest factor that motivated students the most to learn English was the personal factor, the students mentioned that they learnt English because they needed to get a good job, and they also desired to be fluent in English. However, students’ ages, gender and the school which student’s graduation from were no significant motivating to their English learning. And then it is followed by the family factor, teacher’s personality and teaching style factor, and the social factor. In addition, the findings of comparison between year 2 and 3 students shown that there was no different for the strongest factor that influent both years students to learn English as the personal factors. The family factor was also the second strong factor impacting both years were similar. The third strong factor impacting was the teacher’s personality/teaching style factors. These factors influent both years to learn English were slightly different. The social factor was the last factor impacted them to learn English, which were not different.